The alternate-form reliability study of six variants of the Brief Visual-Spatial Memory Test-Revised and the Hopkins Verbal Learning Test-Revised - Cai, Yumei; Yang, Tianlong; Yu, Xin; Han, Xue; Chen, Gong; Shi, Chuan (Frontiers in Public Health, 2023)
Introduction:The revised Hopkins Verbal Learning Test-Revised (HVLT-R) and the Brief Visual-Spatial Memory Test-Revised (BVMT-R) are two widely used tests involving visual, language learning and memory. In the two tests, six different versions are assembled, respectively, to prevent learning effects. Currently, no researchers have compared the six versions of the two tests. In this work, we confirm the equivalence of six HVLT-R and BVMT-R versions. Methods: 20 people accomplish all six HVLT-R and BVMT-R tests, while 120 people are assigned one of the six sets (six HVLT-R and BVMT-R tests) at random. The Intelligence Quotient (IQ) level is measured using the short version of the Wechsler Adult Intelligence test. The K-Related sample test (a nonparametric test) is used to observe the differences in test scores among the 20 subjects. The one-way Analysis of Variance (ANOVA) test is utilized to analyze the differences in test scores among the 120 subjects. The scores on different versions are compared using two similar sample tests. The total number of HVLT-R learning, the total number of HVLT-R delays, the total number of BVMT-R learning, and the total number of BVMT-R delays are indexes for comparison. Version and test scores are used as research factors, while different versions are used as research levels. Results: The results suggest that HVLT-R and BVMT-R versions 3, 5 and 6 are equally difficult, and relatively easy compared to versions 1, 2 and 4. HVLT-R versions 3, 5, and 6 show good reliability and can be used interchangeably when testing word learning ability or short-term memory; BVMT-R Versions 3, 5, and 6 show acceptable reliability and can be replaced. Discussion: In the study of multiple follow-ups, it is a must to avoid discrepant versions and choose other equivalent versions.The results from this study could be used as a guide for upcoming studies and clinical applications in China.